Use of FMEA analysis to reduce risk of errors in prescribing and administering drugs in paediatric wards: a quality improvement report. Issue 6 (18th December 2012) - Lago, Paola; Bizzarri, Giancarlo; Scalzotto, Francesca; Parpaiola, Antonella; Amigoni, Angela; Putoto, Giovanni; Perilongo, Giorgio
Abstract : Objective: Administering medication to hospitalised infants and children is a complex process at high risk of error. Failure mode and effect analysis (FMEA) is a proactive tool used to analyse risks, identify failures before they happen and prioritise remedial measures. To examine the hazards associated with the process of drug delivery to children, we performed a proactive risk-assessment analysis. Design and setting: Five multidisciplinary teams, representing different divisions of the paediatric department at Padua University Hospital, were trained to analyse the drug-delivery process, to identify possible causes of failures and their potential effects, to calculate a risk priority number (RPN) for each failure and plan changes in practices. Primary outcome: To identify higher-priority potential failure modes as defined by RPNs and planning changes in clinical practice to reduce the risk of patients harm and improve safety in the process of medication use in children. Results: In all, 37 higher-priority potential failure modes and 71 associated causes and effects were identified. The highest RPNs related (>48) mainly to errors in calculating drug doses and concentrations. Many of these failure modes were found in all the five units, suggesting the presence of common targets for improvement, particularly in enhancing the safety of prescription and preparation of endovenous drugs. The introductions of new activities in the revised process of administering drugs allowed reducing the high-risk failure modes of 60%. Conclusions: FMEA is an effective proactive risk-assessment tool useful to aid multidisciplinary groups in understanding a process care and identifying errors that may occur, prioritising remedial interventions and possibly enhancing the safety of drug delivery in children.